2006
DOI: 10.1371/journal.pctr.0010011
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Outcomes of a Pilot Randomized Trial of Azithromycin Treatment for Asthma

Abstract: Objectives:The respiratory pathogen Chlamydia pneumoniae (C. pneumoniae) produces acute and chronic lung infections and is associated with asthma. Evidence for effectiveness of antichlamydial antibiotics in asthma is limited. The primary objective of this pilot study was to investigate the feasibility of performing an asthma clinical trial in practice settings where most asthma is encountered and managed. The secondary objectives were to investigate (1) whether azithromycin treatment would affect any asthma ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 28 publications
(30 reference statements)
3
59
1
1
Order By: Relevance
“…Outcomes of the AZMATICS study also support findings of Hahn et al 22 and Sutherland et al, 26 who reported lesser or no benefit associated with macrolide treatment in subjects with mild to moderate asthma. However, all 3 studies were underpowered to detect clinically significant effects in milder asthma.…”
Section: Previous Studiessupporting
confidence: 77%
See 4 more Smart Citations
“…Outcomes of the AZMATICS study also support findings of Hahn et al 22 and Sutherland et al, 26 who reported lesser or no benefit associated with macrolide treatment in subjects with mild to moderate asthma. However, all 3 studies were underpowered to detect clinically significant effects in milder asthma.…”
Section: Previous Studiessupporting
confidence: 77%
“…It is possible that other mechanisms, such as denial, cognitive dissonance, or both, could have promoted systematic misreporting by OL subjects. A true treatment effect is supported by the strength and consistency of the results (including 2 validated instruments, the AQL questionnaire and the asthma control questionnaire), by agreement with our blinded pilot results 22 and by the results of the principal investigator's (DLH) previous prospective observational cohort study that included patients with confirmed C. pneumoniae infections. 38 Although exploratory analyses suggest that smoking may have a significant modifying effect, AZMATICS was underpowered for subgroup analyses.…”
Section: Limitationssupporting
confidence: 67%
See 3 more Smart Citations